Analisis Akuntansi Persediaan Barang Dagangan Pada Toko Baju Bekas Import - Puspitasari, Ayu; Animah, Animah; Astuti, Widia (Fakultas Ekonomi dan Bisnis Unram, 2024)
Inventory is merchandise owned by a company to be resold or processed first and then sold. Inventory management is a normal problem in trading companies. Inventory management is an important problem faced by companies, especially trading companies, therefore inventory must be managed as well as possible. Therefore, in carrying out its business activities, companies need to implement inventory accounting systems and procedures that reflect the elements of internal control. The purpose of this research is to determine whether the method of recording merchandise inventory applied at the Tripical Trift Store is in accordance with SAK EMKM. The data collection methods used were interviews, observation, documentation and literature study. The analysis method uses a qualitative descriptive method. From the research results, the recording of merchandise inventory carried out at the Tropical Trift Store is still simple in relation to the inventory of merchandise. namely, it is not in accordance with the existing recording system in SAK EMKM due to the lack of socialization and understanding of the system.